PENGEMBANGAN APLIKASI PELAYANAN ANTENATAL CARE BAGI IBU HAMIL DI ERA PANDEMI COVID -19 BERBASIS ANDROID DI KAB.BANGKA - Liana Devi Octavia; Ayu Febri. W; Gaipyana Sembiring (Jurnal Ilmiah Kebidanan Imelda, 2023)
The emergence of the COVID-19 pandemic has had an impact on the health service delivery system. The impact of COVID-19 could be greater on vulnerable populations including pregnant women. Pregnant women are afraid to go to health facilities for fear of contracting Covid, suggestions to postpone pregnancy checks and classes for pregnant women, as well as service uncertainty in terms of personnel and infrastructure including personal protective equipment. The aim of this research is to develop an Android-based ANC Service Application for Pregnant Women in the Pandemic Era. This research was carried out at PKM Kenangan, Bangka Regency in May-October 2021. The informants in this study were village midwives and pregnant women. This type of research is qualitative with a research and development approach. The data used in this study are secondary and primary data through Focus Group Discussion with purposive sampling. This research method is RnD (research and development sequential explanatory mixed methods, the first stage is quantitative research then qualitative research is carried out to strengthen the quantitative results. The data used in the quantitative research is secondary data from perinatal mortality and OVP recapitulation, while in qualitative research with interviews in depth by taking purposive sampling. The results showed that information related to the Corona Virus in pregnant women was still minimal and difficult to access, so it was necessary to have a special application related to information related to the Corona Virus in pregnant women. Based on these results, a blue print application model was created and the initial product was in the form of Android-based application regarding guidelines for prenatal care for pregnant women during the COVID-19 pandemic. The conclusion in this study is that information related to antenatal care for pregnant women during the Covid pandemic era is less sick. i antenatal care services for pregnant women during the Corona Virus pandemic 19.